Illuminating an invisible state of the HIV-1 capsid protein CTD dimer using 19 F NMR and weighted ensemble simulations - Darian T. Yang; Lillian T. Chong; Angela M. Gronenborn (Proceedings of the National Academy of Sciences, 2025)
The HIV-1 capsid protein (CA) assembles into a conical shell during viral maturation, encasing and protecting the viral RNA genome. The C-terminal domain (CTD) of the two-domain capsid protein dimerizes, and this dimer connects individual chains in the mature capsid lattice. Previous NMR studies have shown that different dimer arrangements can be formed by isolated capsid protein chains and in assembled capsid lattices; however, the dynamics and functional relevance of these alternate dimers are unknown. To explore the conformational landscape of the CA-CTD dimer, we carried out atomistic molecular dynamics simulations using the weighted ensemble path sampling strategy, generating an ensemble of conformations. Focusing on the two dimer forms previously observed via solution NMR, we refined the conformational ensemble to highlight two metastable states using a Markov state model. Experimentally, we measured the interconversion rates between the two alternate dimers using 19 F NMR, and these rates showed good agreement with the interconversion rates derived from the simulations. After identifying the key interactions that distinguish the dimer states, the alternate dimer was further experimentally verified through disulfide crosslinking. Our results demonstrate the advantages of pairing weighted ensemble path sampling with 19 F NMR to gain atomistic insights into the hidden dimer state of the HIV-1 capsid protein.